An electrically active gecko-effect soft gripper under a low voltage by mimicking gecko's adhesive structures and toe muscles. Issue 24 (20th May 2020) - Tian, Hongmiao; Liu, Haoran; Shao, Jinyou; Li, Shuai; Li, Xiangming; Chen, Xiaoming
Abstract : An electrically active gecko-effect soft gripper under a low voltage based on adhesive structures and liquid crystal elastomers. Abstract : With the combination of the passive adhesion generated by micro/nano-structures at their feet and the active mechanical stimulus of their toe muscles, geckos can stably walk on vertical walls and horizontal ceilings. Inspired by such stimuli-responsive systems in nature, an active adhesive soft gripper stimulated by low voltage (usually ≤6 V), consisting of a passive mushroom-like adhesive structure and an electrically active liquid crystal elastomer working as toe muscles, is proposed in this study. Through voltage on/off switching, reversible deformation can be generated for switchable adhesion, where high adhesion can be achieved under the action of a preload force accompanied by a 0 V voltage and low adhesion can be obtained under an exerted voltage. This gecko-inspired soft gripper was tested and found to be successful as a transport device for gripping/releasing objects with different features, such as a glass ball, a sample bottle, and a steel weight. To the best of our knowledge, the present study is the first to propose an electrically active gecko-inspired soft gripper for transferring objects with different surfaces by the control of low voltage, processing great application potential in industrial lines and daily life and providing a novel perspective on soft gripper design.